The Homo Sapiens Seafarer Diaspora in the Southeast Asian Archipelago: Traversing Transoceanic Waters from the Mesolithic to the Neolithic Era - Ali, Ismail; Abdullah, Mohd Firdaus (UUM PRESS, 2024)
This study delves into the profound impact of waters, seas, and oceans on the historical trajectory of Southeast Asia, challenging the prevailing narratives that have often overlooked the vital contributions of the region’s seafaring ancestors. Traditionally dismissed as mere sources of inspiration, these maritime expanses were instrumental in shaping the transition from traditional kingdoms to modern nation-states in Southeast Asia. While historical theories such as the Out of Yunan and Out of Taiwan paradigms proposed by Western scholars have dominated discussions on the development of traditional civilizations in the Southeast Asian Archipelago (Nusantara), this paper advocates for a Southeast Asia-centric perspective to rectify the marginalization of historical realities. The narrative encompasses the ancient epoch and prehistoric eras marked by the migrations of Homo erectus and Homo sapiens from mainland Asia, providing a comprehensive understanding of the early evolution of maritime civilizations in the region. This exploration highlights the risks and sacrifices made by seafaring communities from B.C. to A.D., as they navigated treacherous waters and stormy weathers to ensure the legacy and continuity of future generations. Far from being trivial, their millennia-long contributions have been likened to “shipwrecks laying at the bottom of the sea in their forgotten watery graves.” By elucidating how these communities utilized seas and oceans as sources of emancipation and development, this study aims to reposition Southeast Asia as an epicentre of civilization, rivalling any in the ancient world. Ultimately, this research provides a nuanced perspective on the region’s maritime history, challenging existing paradigms and contributing to the broader international discourse on the development of civilizations